Mischka's war : a story of urvival from war-torn Europe to New York - Fitzpatrick, Sheila (London : I.B. Tauris & Co. Ltd, 2017)
"In 1943, 22-year-old Latvian Mischka Danos chanced on a terrible sight - a pit filled with the bodies of Jews killed by the occupying Germans. A few months later, escaping conscription into the Waffen-SS in Riga, Mischka entered Hitler's Reich itself on a student exchange to Germany. There, as the war drew to an end, he narrowly escaped death in the Allied fire-bombing of Dresden. As he made his escape from Hitler's Reich he fell ill and was incarcerated in hospital before finally reuniting with his resourceful mother Olga, who had made her own way out of Riga, saving some Jews along the way. The diaries, correspondence and later recollections of mother and son provide a vivid recreation of life in occupied Germany, where anxiety, fear and loss were tempered by friendship, and where the ineptitude of international and occupation bureaucracies added its own touch of black humour. Sponsored as immigrants by one of the Jews Olga had saved, they eventually reached New York in the early 1950s. As refugee experiences go, they were among the lucky ones--but even luck leaves scars. The author, who met and married Mischka forty years after these events, turns her skills as a historian and wry eye as a memoirist to telling this remarkable story."--
Family -- Childhood -- Riga under the Soviets -- Riga under the Germans -- Wartime Germany -- The bombing of Dresden -- Displaced persons in Flensburg -- Olga, from Flensburg to Fulda -- Student in Hanover -- Physics and marriage in Heidelberg -- Olga's departure -- Mischka's departure -- Afterword.
Online resource; title from PDF title page (EBSCO, viewed July 13, 2017).
Includes bibliographical references and index.
Keywords: Danos, Mischka; World War, 1939-1945 -- Refugees; Refugees -- Europe -- Biography; Latvia -- History -- German occupation, 1941-1944.; Guerre mondiale, 1939-1945 -- Réfugiés.; Réfugiés -- Europe -- Biographies; Lettonie -- Histoire -- 1941-1944 (Occupation allemande); BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- Europe -- Western; Refugees; Europe; Latvia; 1939-1945; collective biographies; Biographies; History; Biographies; Biographies